2021
DOI: 10.1038/s43246-021-00212-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous origami-architected materials with variable stiffness

Abstract: Origami, the ancient art of paper folding, has shown its potential as a versatile platform to design various reconfigurable structures. The designs of most origami-inspired architected materials rely on a periodic arrangement of identical unit cells repeated throughout the whole system. It is challenging to alter the arrangement once the design is fixed, which may limit the reconfigurable nature of origami-based structures. Inspired by phase transformations in natural materials, here we study origami tessellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, the preceding discussion serves as a coarse approximation to designing a waterbomb tessellation with targeted mechanical properties. Related work that uses origami to achieve programmable stiffness includes Zhai et al [25] via curved crease origami, Wen et al [27] and Miyazawa et al [26] via stacked and cellular origami. In flat foldable, quadrilateral origami, it has been shown that the prescribing fold angles at the boundary uniquely determines the kinematics of the entire sheet [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preceding discussion serves as a coarse approximation to designing a waterbomb tessellation with targeted mechanical properties. Related work that uses origami to achieve programmable stiffness includes Zhai et al [25] via curved crease origami, Wen et al [27] and Miyazawa et al [26] via stacked and cellular origami. In flat foldable, quadrilateral origami, it has been shown that the prescribing fold angles at the boundary uniquely determines the kinematics of the entire sheet [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Origami has emerged as an important platform in science and engineering for applications across a diverse array of length scales: from large-scale aerospace applications [1,2] to smallerscale biomedical applications [3,4]. In particular, the multistability properties of origami have proven useful for the design of deployable structures that are stable in both their compact and deployed configurations [5,6], driving locomotion in origami-based robotics [7][8][9][10], storing mechanical energy [11] and information [12][13][14], and for origami-based mechanical metamaterials [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rich design space, origami structures have been a major source of inspiration for creating metamaterial microstructures with various symmetry types. [23][24][25][26][27][28][29][30] In the literature, some tubular origami-based metamaterials have been created to achieve triclinic symmetry. [31] However, the disadvantage of tubular designs is that their unit cell geometry and configuration space are typically intricate, involving several parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The triclinic symmetry describes a periodic system whose primitive vectors are of unequal length, and the angles between these vectors are all different and may not even include 90 • . Due to its rich design space, origami structures have been a major source of inspiration for creating metamaterial microstructures with various symmetry types [23,24,25,26,27,28,29,30]. In the literature, some tubular origami-based metamaterials have been created to achieve triclinic symmetry [31].…”
Section: Introductionmentioning
confidence: 99%
“…The unit cell-based approach to analyzing periodic lattices has been widely adopted in the literature. [8][9][10][11][12] These materials have tunable mechanical properties as the global-level physical behavior is not only dependent upon the intrinsic material, but the microstructural geometry of the periodic units also. The macro-scale lattice properties like Young's moduli, [13,14] Poisson's ratio, [15] and shear moduli [16] are largely dependent upon the geometric configurations of the periodic unit cells.…”
Section: Introductionmentioning
confidence: 99%